Learning Styles of Ho Chi Minh City University of Technical Education Students - Đỗ Mạnh Cường; Nguyễn Hữu Minh Luân (Journal of Technical Education Science, 2006)
Students analysing is an important step in instructional design process. In this step, the determination of students’ learning style is required. This paper presents some characteristics of learning style of students in Ho Chi Minh City University for Teachnical Education. From this result we can show points should be focused to about teaching methods to improve and enhance learning achivements of students. In this observation, we used ILS tool (Index Learning Style) developed by Richard M. Felder and Barbara A. Soloman from The North Carolina State University